Rituximab-Induced Bronchiolitis Obliterans Organizing Pneumonia - Ahmet B. Ergin; Nancy Fong; Hamed A. Daw (Case Reports in Medicine)
Rituximab-induced lung disease (R-ILD) is a rare entity that should be considered in patients treated with rituximab who present with dyspnea, fever, and cough, but no clear evidence of infection. A variety of pathologic findings have been described in this setting. Bronchiolitis obliterans organizing pneumonia (BOOP) is the most common clinicopathologic diagnosis, followed by interstitial pneumonitis, acute respiratory distress syndrome (ARDS), and hypersensitivity pneumonitis. Prompt diagnosis and treatment with corticosteroids are essential as discussed by Wagner et al. (2007). Here we present a case of an 82-year-old man who was treated with rituximab for recurrent marginal zone lymphoma. After the first infusion of rituximab, he reported fever, chills, and dyspnea. On computed tomography imaging, he was found to have bilateral patchy infiltrates, consistent with BOOP on biopsy. In our patient, BOOP was caused by single-agent rituximab, in the first week after the first infusion of rituximab. We reviewed the relevant literature to clarify the different presentations and characteristics of R-ILD and raise awareness of this relatively overlooked entity.